National interest organisations in EU policy-making. Issue 5 (3rd September 2017) - Eising, Rainer; Rasch, Daniel; Rozbicka, Patrycja
Abstract: Comparative and EU interest group studies are marked by a progression towards theory-driven, large- N empirical studies in the past 20 years. With the study of national interest organisations in EU policy-making, this special issue puts centre stage a theoretically and empirically neglected topic in this research field. The individual contributions include interest group characteristics, institutional contexts as well as issue contexts as explanatory factors in their empirical analyses of multilevel interest representation. They present novel developments in the study of political alignments among interest groups and political institutions, the Europeanisation of domestic interest organisations, and the question of bias in interest group populations. Thereby, they not only contribute to the comparative study of interest groups, but also to the analysis of policy-making, multilevel governance, and political representation in the EU.